Rock core nano-film as well as preparation method and application thereof
By preparing core nanofilms, the data deviation and poor reproducibility of the wettability measurement of the tight reservoir in the prior art are solved, and direct and accurate measurement of the wettability contact angle of the core is achieved, and the accuracy and reproducibility of the measurement are improved.
Patent Information
- Application Number
- CN202311090048.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art has problems of data deviation and poor reproducibility when measuring the wettability of tight reservoirs, especially the contact angle method and the Washburn powder method.
A method of preparing core nanofilm is adopted to form a Langmuir film through ball milling and organic solvent dispersion treatment and transfer it to a solid matrix to obtain a dense and uniform single-layer film, realizing direct and accurate measurement of core wet contact angle.
Direct and accurate measurement of core wet contact angles is achieved, the accuracy and reproducibility of measurement are improved, and the wettability of rock can be accurately evaluated.
Smart Images

Figure CN119534059A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of measurement methods for reservoir wettability characterization, and in particular relates to a core nano-film and a preparation method and application thereof. Background Art
[0002] As the exploitation time increases, tight oil reservoirs have gradually become the main source of crude oil. In order to ensure energy security, it is necessary to carry out highly targeted, forward-looking and innovative research on several major technical problems and key scientific theoretical issues in the exploitation of tight oil reservoirs, strengthen technical reserves, and thus lay a good foundation for improving the scientific and technological independent innovation capabilities and core competitiveness of the petroleum and petrochemical industry.
[0003] The wettability of oil layers is the most basic surface property of the pores of oil layer rocks. It is an important parameter for describing the seepage channel and an important factor affecting the oil-water seepage behavior. Therefore, in order to achieve a deep understanding of the seepage channel and seepage mechanism of tight oil reservoirs, it is necessary to accurately and quantitatively describe the wettability of oil layers. At present, there are three common methods used for measuring the wettability of conventional reservoirs: contact angle method, Amott method, USBM method and a series of improved methods. In addition to the above three methods, many scholars have also developed some other measurement methods for measuring reservoir wettability. Among them, the quantitative measurement methods include self-imbibition rate method, nuclear magnetic resonance method and relative permeability method; the qualitative measurement methods include low-temperature electron scanning method, glass slide method, Wihelmy dynamic plate method, Washburn powder method, microporous membrane method, automatic imbibition method, logging method, flotation method and staining method.
[0004] Although people have obtained some guiding experimental data in the study of wettability of tight oil reservoirs using the above methods, these methods all have defects that cannot be ignored. For the contact angle measurement method, since the core is a porous material, the data we measured is not the contact angle of water or oil on a uniform plane. Its size reaction is not completely determined by the wettability of the liquid on the solid surface, and the gas in the pores has an important influence on the size of the measured value. Therefore, the contact angle data obtained by this method will have a large deviation from the actual wettability of the reservoir. For the Washburn powder method, the experimental results are greatly affected by powder size, filling density, etc., and the above factors are difficult to control, resulting in poor reproducibility of the experimental results; in addition, since it is difficult to find a standard sample to calibrate and compare the experimental results obtained, this method can qualitatively describe the change in sample wettability, but it is difficult to quantitatively explain the change in wettability. For the NMR method, it is an indirect description method. When comparing the wettability between different samples, the accuracy is sometimes not satisfactory. In addition, its experimental efficiency is low. For unconventional reservoirs, the measurement results cannot represent the overall characteristics of the rock sample. Therefore, it is very urgent to develop a new technology to detect the wettability of tight oil reservoirs in order to obtain the rock wettability and its changing law that is more in line with the actual situation.
[0005] For wettability generally measured by contact angle method, the measurement principle is: process the sample to be tested into a thin plate, and polish its surface to eliminate the influence of surface roughness on the wetting angle. Immerse in oil or water. Drop a drop of liquid with a diameter of about 1 to 2 mm on the smooth surface of the rock, magnify the droplet through a microscope, take a picture of the shape of the droplet, and then measure the contact angle. The size of the contact angle (θ) is used to judge the difference in cognition. When 0°<θ<75°, it is water wetting; when 75°<θ<105°, it is neutral wetting; when 105°<θ<180°, it is oil wetting.
[0006] Ahmed et al. used micron-resolution X-ray tomography images based on reservoirs, extracted surface grid images by segmenting pixels, and then used automatic algorithms to process the measured three-dimensional pore-scale images to measure contact angles, interface curvatures, and surface roughness. The measurement results obtained by computer automation algorithms were consistent with the experimental measurement results. Bordba et al. measured the contact angle of 10μL pure water droplets through a digital microscope when studying composite coatings on titanium substrates, and determined the wettability changes, which decreased with the increase of graphene content in the composite coatings. Aghajanzadeh et al. used the stationary drop method to measure the application of silica nanoparticles in the wettability change of oil-wet carbonate rocks. The contact angle and spontaneous absorption experiments and electron microscopy analysis showed that nanoparticles can change wettability. Hou et al. used the sessile drop method to measure the wettability changes after the oil droplets were treated with surfactants of different concentrations when studying the synergistic effect of cationic surfactants and non-ionic surfactants; the synergistic effect between cationic surfactants and non-ionic surfactants was studied. Dundar et al. also used the droplet placement method to measure the wetting angle when studying the TiO2 film deposited on window glass for air purification and self-cleaning applications, and explored the superhydrophilic properties of TiO2 films under different spraying conditions. Zhang et al. studied the selective laser melting of nanocomposites, changed their surface morphology, roughness, wettability and corrosion resistance, analyzed their wetting behavior after modification, and used the droplet placement method to test their modified surface morphology. Ali et al. measured the surface wettability of FeCrAl samples oxidized under different simulated light water reactor water chemistry conditions to predict the critical heat flux of pool boiling. When performing surface wettability analysis, they used the energy model expression of solid, liquid and gas interfaces developed by Tadmor et al. The model consists of three equations that relate the droplet volume, interface energy, and advancing and receding angles to the equilibrium line energy; this expression can be used to calculate the equilibrium static contact angle by inverse calculation of the known advancing and receding contact angles. Chang et al. analyzed the contact angle measurement method and found that it relies on image processing, which has inherent errors due to optical limitations, especially near the contact line. Boris et al. used the tilted plate method to determine the contact angle. By comparing the tilted sliding angles of two-dimensional droplets that are still in equilibrium at various tilt angles, they concluded that the contact angles of the upper and lower contact lines are not always equal to the retreating and advancing contact angles. In addition, Deglint et al. used micrometer CT technology to carry out microscopic wettability measurement at the pore scale. This technology can well demonstrate the distribution characteristics of actual rock pore wettability, but the technology is still immature and has many imperfections.
[0007] The wettability determination method based on the contact angle method is a classic detection method for wettability characterization and determination. According to reports, it has been widely used in the field of detection. Its basic principle is to place the fluid on the surface of the object to be tested, and to measure the contact angle to reflect the wettability. Among them, due to the influence of the surface roughness of the object to be measured, the overall measurement angle will have an error of about 10°. Commonly used methods include contact angle method, Amott-Harvey method, nuclear magnetic resonance method, logging curve method, USBM method, etc.
[0008] However, in previous studies and measurements of wettability angles, the wettability values obtained based on the measurement angles were extremely inaccurate due to the influence of surface morphology. In addition, previous research methods did not directly describe the wettability of the reservoir, but rather used indirect calculation methods, which resulted in the inability to accurately describe the wettability characteristics of the reservoir.
[0009] Therefore, developing a high-precision core surface treatment method that can accurately, quickly and easily measure the core wettability contact angle is an urgent problem that technicians in this field need to solve. Summary of the invention
[0010] The purpose of the present invention is to provide a core nanofilm and a preparation method and application thereof. The reservoir core processed by the preparation method can obtain a single-layer film composed of a stable, uniform and dense surface morphology, and does not change the key components that affect the wettability factors, thereby realizing direct and accurate measurement of the wettability contact angle of the core.
[0011] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a method for preparing a core nanofilm, the preparation method comprising:
[0013] (1) mixing the ball-milled core with an organic solvent to obtain a dispersion;
[0014] (2) vertically immersing the hydrophilically modified solid substrate under the liquid surface, spreading the dispersion obtained in step (1) on the liquid surface of the LB tank and allowing it to stand, and then performing a film pressing process on the dispersion to obtain a Langmuir film;
[0015] (3) Lifting the solid substrate described in step (2) so that the Langmuir film described in step (3) is transferred to the solid substrate, and the core nanofilm is obtained after standing.
[0016] In the present invention, the LB trough is the abbreviation of Langmuir-Blodgett trough.
[0017] The preparation method provided by the present invention disperses and compresses the core particles, and then uses a solid supporting matrix to obtain a dense and uniform single-layer film. The processed reservoir core can obtain a single-layer film composed of a stable, uniform and dense surface morphology, and does not change the key components that affect the wettability factors, thereby achieving direct and accurate measurement of the wettability contact angle of the core; at the same time, it also has the advantages of being able to accurately control the composition, thickness and component deposition order of the core nanofilm.
[0018] As a preferred technical solution of the present invention, when performing the ball milling in step (1), the injection amount of the core is 2-5g, for example, it can be 2.5g, 3g, 3.5g, 4g or 4.5g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] Preferably, the rotation speed of the ball mill in step (1) is 350-500 r / min, for example, it can be 370 r / min, 400 r / min, 420 r / min, 450 r / min, 470 r / min or 490 r / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Preferably, the ball milling time in step (1) is 195-325 min, for example, it can be 200 min, 205 min, 225 min, 250 min, 275 min, 300 min or 315 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] In the present invention, the ball milling cycle is 1-10 minutes of stopping time for every 60 minutes of grinding or 1-5 minutes of stopping time for every 30 minutes of grinding.
[0022] As a preferred technical solution of the present invention, after the ball milling in step (1), the size of the core is 350-950nm, for example, it can be 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm or 900nm, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0023] Preferably, the organic solvent in step (1) comprises chloroform.
[0024] In the present invention, chloroform is selected as the dispersion solution because chloroform has good dispersibility, is very volatile at room temperature and is helpful in forming core particles.
[0025] Preferably, the mixing in step (1) is performed under ultrasound.
[0026] Preferably, the mixing time in step (1) is 25-35 min, for example, it can be 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min or 34 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the concentration of the dispersion in step (1) is 0.01-0.08 mg / mL, for example, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL or 0.07 mg / mL, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] As a preferred technical solution of the present invention, the material of the solid substrate in step (2) includes any one of a quartz sheet, a conductive glass, a silicon single crystal sheet, a mica sheet or a metal sheet.
[0029] Preferably, the conductive glass includes ITO conductive glass and / or FTO conductive glass.
[0030] Preferably, the metal sheet includes any one of a Cu sheet, a Ti sheet, a Ni sheet or an Al sheet.
[0031] In the present invention, the solid matrix is cut into required sizes before use; the solid matrix is a solid base material that is hard and impermeable.
[0032] Preferably, the method for hydrophilic modification of the solid substrate in step (2) comprises: sequentially performing a first cleaning treatment, a plasma treatment and a second cleaning treatment on the solid substrate.
[0033] Preferably, the plasma treatment is: bombarding the surface of the solid substrate with plasma for 8-12 minutes.
[0034] In the present invention, the steps of the first cleaning treatment and the second cleaning treatment are not specifically limited, as long as the impurities on the surface of the solid substrate can be cleaned; in step (2), the hydrophilically modified solid substrate is placed in distilled water for standby use.
[0035] As a preferred technical solution of the present invention, the depth of the solid matrix vertically immersed under the liquid surface in step (2) is 1.5-5 cm, for example, it can be 2 cm, 2.5 cm, 3 cm, 3.5 cm, 4 cm or 4.5 cm, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] Preferably, the distance between the solid substrate and the LB tank in step (2) is 0.5-1 cm, for example, 0.6 cm, 0.7 cm, 0.8 cm or 0.9 cm, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the volume of the dispersion in step (2) is 50-250 μL, for example, it can be 70 μL, 90 μL, 100 μL, 120 μL, 150 μL, 170 μL, 190 μL, 200 μL, 220 μL or 240 μL, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] It is worth noting that, in the present invention, the chloroform dispersion containing core nanoparticles is dropped onto the water surface of the LB tank using a microsyringe. Since chloroform has a low boiling point and evaporates easily, after the dispersion is transferred to the water surface, wait for about 2-5 minutes until the chloroform evaporates, only the nanocore particles are left on the water surface of the LB tank, and the nanocore particles are randomly dispersed and arranged on the water surface.
[0039] Preferably, the standing time in step (2) is ≥10 min, for example, it can be 11 min, 12 min, 13 min, 14 min, 15 min, 17 min or 20 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] As a preferred technical solution of the present invention, the speed of the lamination treatment in step (2) is 5-80 mm / min, for example, it can be 10 mm / min, 20 mm / min, 30 mm / min, 40 mm / min, 50 mm / min, 60 mm / min or 70 mm / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the surface pressure of the Langmuir film in step (2) is 5-35 mN / m, for example, it can be 10 mN / m, 15 mN / m, 20 mN / m, 25 mN / m or 30 mN / m, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] It is worth noting that the compression treatment by the sliding barriers on both sides of the LB trough will gradually make the core nanoparticles originally randomly distributed on the water surface arranged tightly. Through the compression process, the state of the particles being far apart is broken, the surface area of the overall particles arranged on the water surface becomes smaller, and the particles are gradually denser, thus forming a two-dimensional planar film state. When compressed to a certain area, the particles are closely arranged in two dimensions (such as Figure 3At this time, the control curve of surface pressure and area is observed through the computer control terminal connected to the film pulling instrument. When the slope of the curve becomes steeper, the appropriate surface pressure range is selected as the optimal film pulling pressure at this time.
[0043] As a preferred technical solution of the present invention, the lifting pressure in step (3) is 5-35mN / m, for example, it can be 10mN / m, 15mN / m, 20mN / m, 25mN / m or 30mN / m, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In the present invention, the lifting pressure in step (3) is consistent with the surface pressure of the Langmuir film in step (2).
[0045] Preferably, the lifting speed in step (3) is 1.5-22.5 mm / min, for example, it can be 3 mm / min, 5 mm / min, 7 mm / min, 10 mm / min, 12 mm / min, 15 mm / min, 17 mm / min or 20 mm / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0046] In the present invention, in step (3), the solid substrate is lifted at a uniform speed, and the mechanical cantilever holding the solid substrate is slowly raised by controlling the computer control end, so that the solid substrate previously vertically inserted below the water surface is slowly lifted at a uniform speed, thereby realizing the process of transferring the two-dimensional film dispersed on the water surface to the solid substrate.
[0047] Preferably, the end point of lifting in step (3) is that the solid matrix is completely lifted to the water surface.
[0048] Preferably, the standing time in step (3) is ≥10 min, for example, it can be 11 min, 12 min, 13 min, 14 min, 15 min, 17 min or 20 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] Preferably, the thickness of the core nanofilm in step (3) is less than 1000 nm, for example, it can be 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm or 900 nm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] As a preferred technical solution of the present invention, the preparation method comprises:
[0051] (1) ball milling the core at a speed of 350-500 r / min for 195-325 min to obtain core particles with a size of 350-950 nm, and then mixing the organic solvent and the core particles under ultrasound for 25-35 min to obtain a dispersion with a concentration of 0.01-0.08 mg / mL;
[0052] (2) vertically immersing the hydrophilically modified solid substrate under the liquid surface, spreading 50-250 μL of the dispersion obtained in step (1) on the liquid surface of the LB tank and letting it stand for ≥10 min, and then pressing the dispersion at a speed of 5-80 mm / min to obtain a Langmuir film with a surface pressure of 5-35 mN / m;
[0053] The depth of the solid matrix vertically immersed in the liquid surface is 1.5-5 cm; the distance between the solid matrix and the LB tank is 0.5-1 cm;
[0054] (3) The solid substrate of step (2) is lifted at a pressure of 5-35 mN / m and a speed of 1.5-22.5 mm / min, so that the Langmuir film of step (2) is transferred to the solid substrate, until the solid substrate is completely lifted out of the water surface, and after standing for ≥10 min, a core nanofilm with a thickness of less than 1000 nm is obtained.
[0055] In a second aspect, the present invention provides a core nanofilm, wherein the core nanofilm is prepared by the preparation method described in the first aspect;
[0056] The thickness of the core nano film is less than 1000 nm.
[0057] The core nanofilm prepared by the present invention is a dense and uniform single-layer film, which can directly measure the core contact angle, eliminating the complex processing process in the traditional core wettability measurement method, and can realize rapid detection of the sample to be tested.
[0058] In a third aspect, the present invention provides an application of the core nanofilm as described in the second aspect, wherein the core nanofilm is used for evaluating rock wettability.
[0059] When the present invention evaluates the wettability of rocks, the samples are the core nano-film and the supporting solid matrix.
[0060] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] The reservoir core processed by the preparation method provided by the present invention can obtain a single-layer film composed of a stable, uniform and dense surface morphology, and does not change the key components that affect the wettability factors, thereby realizing direct and accurate measurement of the wettability contact angle of the core, and then accurately evaluating the wettability of the rock; the preparation method is simple to operate, the conditions are mild, and the composition, thickness and component deposition order of the core nanofilm can be accurately controlled. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 A schematic diagram of the structure of the LB tank provided by the present invention;
[0064] Among them, 1-LB trough, 2-Wilhelmy balance, 3-subphase, 4-slip barrier;
[0065] Figure 2 A schematic diagram of the process of performing film pressing on a dispersion provided by the present invention;
[0066] Figure 3 A schematic diagram of the mechanism of performing film pressing treatment on a dispersion provided by the present invention;
[0067] Figure 4 A schematic diagram of the process of lifting a solid substrate and simultaneously lifting a Langmuir film provided by the present invention;
[0068] Figure 5 This is an optical photograph of the sample prepared in Example 1 of the present invention;
[0069] Figure 6 This is an optical photograph of the sample prepared in Example 2 of the present invention;
[0070] Figure 7 This is an optical photograph of the sample prepared in Example 3 of the present invention;
[0071] Figure 8 This is an optical photograph of the sample prepared in Example 4 of the present invention;
[0072] Fig. 9 This is an optical photograph of the sample prepared in Example 5 of the present invention;
[0073] Fig.10 This is an optical photograph of the sample prepared in Example 6 of the present invention;
[0074] Fig.11 This is an optical photograph of the sample prepared in Example 7 of the present invention;
[0075] Fig.12 This is an optical photograph of the sample prepared in Example 8 of the present invention;
[0076] Fig.13 This is an optical photograph of the sample prepared in Example 9 of the present invention;
[0077] Fig.14 This is an optical photograph of the sample prepared in Example 10 of the present invention;
[0078] Fig.15 This is an optical photograph of the sample prepared in Example 11 of the present invention.
[0079] Fig.16 This is an optical photograph of the sample prepared in Example 12 of the present invention.
[0080] Fig.17 This is an optical photograph of the sample prepared in Example 13 of the present invention. DETAILED DESCRIPTION
[0081] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0082] The present invention provides a method for preparing a core nanofilm, the preparation method comprising:
[0083] (1) ball milling the core at a speed of 350-500 r / min for 195-325 min to obtain core particles with a size of 350-950 nm, and then mixing the organic solvent and the core particles under ultrasound for 25-35 min to obtain a dispersion with a concentration of 0.01-0.08 mg / mL;
[0084] (2) The hydrophilically modified solid matrix is vertically immersed under the liquid surface, and 50-250 μL of the dispersion obtained in step (1) is spread on an LB tank (such as Figure 1 The dispersion is placed on the liquid surface and allowed to stand for ≥10 min, and then the dispersion is subjected to film pressing at a speed of 5-80 mm / min (as shown in FIG. Figure 2-3 As shown), a Langmuir film with a surface pressure of 5-35 mN / m is obtained;
[0085] The depth of the solid matrix vertically immersed in the liquid surface is 1.5-5 cm; the distance between the solid matrix and the LB tank is 0.5-1 cm;
[0086] (3) lifting the solid substrate of step (2) at a pressure of 5-35 mN / m and a speed of 5-80 mm / min, so that the Langmuir film of step (2) is transferred to the solid substrate (e.g. Figure 4 As shown), until all the solid matrix is lifted out of the water, the core nanofilm is obtained after standing for ≥10 minutes.
[0087] Example 1
[0088] This embodiment provides a method for preparing a core nanofilm, the preparation method comprising:
[0089] (1) 2 g of core was ball-milled at a speed of 500 r / min for 325 min, with a 5-min break after every 30 min of grinding to obtain core particles with a size of 350 nm, which were then added to chloroform and mixed under ultrasound for 30 min to obtain a dispersion with a concentration of 0.02 mg / mL;
[0090] (2) After cutting a quartz sheet of 25×40 mm into pieces of 12.5×40 mm, the quartz sheet was subjected to a first cleaning treatment, plasma bombardment of the surface of the quartz sheet for 10 min, and a second cleaning treatment to obtain a hydrophilically modified quartz sheet;
[0091] The first cleaning treatment is: cleaning the quartz plate with a large amount of distilled water, then putting it into a beaker and adding ethanol until the quartz plate is immersed, then putting the beaker into an ultrasonic cleaner and shaking for 20 minutes, taking out the quartz plate and cleaning the surface with distilled water, and then putting it into concentrated sulfuric acid and heating it at 50°C for 20 minutes;
[0092] The second cleaning treatment is: placing the quartz plate in ethanol for ultrasonic treatment for 20 minutes, then cleaning the surface of the quartz plate with distilled water, and then ultrasonically cleaning it in distilled water for 20 minutes;
[0093] (3) vertically immersing the quartz plate obtained in step (2) into the water at a depth of 2 cm, using a microsyringe to absorb 150 μL of the dispersion obtained in step (1), spreading it on the water surface of the LB tank and letting it stand for 10 min, and then using an LB film lifter to press the dispersion at a speed of 5 mm / min to obtain a Langmuir film with a surface pressure of 25 mN / m;
[0094] The distance between the quartz plate and the LB tank is 0.7 cm;
[0095] (4) Using a clamp, the quartz plate in step (3) is lifted at a constant speed of 22.5 mm / min at a pressure of 25 mN / m, so that the Langmuir film in step (3) is transferred to the quartz plate. After the quartz plate is completely lifted out of the water, the film lifting is stopped and the film is allowed to stand for 10 minutes to obtain the core nanofilm (such as Figure 5 shown);
[0096] There is no particular order in which steps (1) and (2) are performed.
[0097] Example 2
[0098] This embodiment provides a method for preparing a core nanofilm, the preparation method comprising:
[0099] (1) 2 g of core was ball-milled at a speed of 500 r / min for 260 min, with a 2-min break after every 30 min of grinding to obtain core particles with a size of 550 nm, which were then added to chloroform and mixed under ultrasound for 30 min to obtain a dispersion with a concentration of 0.02 mg / mL;
[0100] (2) After cutting a quartz sheet of 25×40 mm into pieces of 12.5×40 mm, the quartz sheet was subjected to a first cleaning treatment, plasma bombardment of the surface of the quartz sheet for 10 min, and a second cleaning treatment to obtain a hydrophilically modified quartz sheet;
[0101] The steps of the first cleaning process and the second cleaning process are the same as those in Example 1;
[0102] (3) vertically immersing the quartz plate obtained in step (2) into the water at a depth of 2 cm, using a microsyringe to absorb 150 μL of the dispersion obtained in step (1), spreading it on the water surface of the LB tank and letting it stand for 10 min, and then using an LB film lifter to press the dispersion at a speed of 20 mm / min to obtain a Langmuir film with a surface pressure of 25 mN / m;
[0103] The distance between the quartz plate and the LB tank is 0.7 cm;
[0104] (4) Using a clamp, the quartz plate in step (3) is lifted at a constant speed of 11.2 mm / min at a pressure of 25 mN / m, so that the Langmuir film in step (3) is transferred to the quartz plate. After the quartz plate is completely lifted out of the water, the film lifting is stopped and the film is allowed to stand for 10 minutes to obtain the core nanofilm (such as Figure 6 shown);
[0105] There is no particular order in which steps (1) and (2) are performed.
[0106] Example 3
[0107] This embodiment provides a method for preparing a core nanofilm, the preparation method comprising:
[0108] (1) 3 g of core was ball-milled at a speed of 400 r / min for 260 min, with a 1 min break after every 30 min of grinding to obtain core particles with a size of 650 nm, which were then added to chloroform and mixed under ultrasound for 30 min to obtain a dispersion with a concentration of 0.01 mg / mL;
[0109] (2) After cutting a quartz sheet of 25×40 mm into pieces of 12.5×40 mm, the quartz sheet was subjected to a first cleaning treatment, plasma bombardment of the surface of the quartz sheet for 10 min, and a second cleaning treatment to obtain a hydrophilically modified quartz sheet;
[0110] The steps of the first cleaning process and the second cleaning process are the same as those in Example 1;
[0111] (3) vertically immersing the quartz plate obtained in step (2) into water at a depth of 1.5 cm, using a microsyringe to absorb 250 μL of the dispersion obtained in step (1), spreading it on the water surface of the LB tank and letting it stand for 10 min, and then using an LB film lifter to press the dispersion at a speed of 80 mm / min to obtain a Langmuir film with a surface pressure of 20 mN / m;
[0112] The distance between the quartz plate and the LB tank is 0.7 cm;
[0113] (4) Using a clamp, the quartz plate in step (3) is lifted at a constant speed of 7.5 mm / min at a pressure of 20 mN / m, so that the Langmuir film in step (3) is transferred to the quartz plate. After the quartz plate is completely lifted out of the water, the film lifting is stopped and the film is allowed to stand for 10 minutes to obtain the core nanofilm (such as Figure 7 shown);
[0114] There is no particular order in which steps (1) and (2) are performed.
[0115] Example 4
[0116] This embodiment provides a method for preparing a core nanofilm, the preparation method comprising:
[0117] (1) 5 g of core was ball-milled at a speed of 350 r / min for 195 min, with a 5-min break after every 60 min of grinding to obtain core particles with a size of 800 nm, which were then added to chloroform and mixed under ultrasound for 30 min to obtain a dispersion with a concentration of 0.01 mg / mL;
[0118] (2) After cutting a quartz sheet of 25×40 mm into pieces of 12.5×40 mm, the quartz sheet was subjected to a first cleaning treatment, plasma bombardment of the surface of the quartz sheet for 10 min, and a second cleaning treatment to obtain a hydrophilically modified quartz sheet;
[0119] The steps of the first cleaning process and the second cleaning process are the same as those in Example 1;
[0120] (3) vertically immersing the quartz plate obtained in step (2) into water at a depth of 1 cm, using a microsyringe to absorb 50 μL of the dispersion obtained in step (1), spreading it on the water surface of the LB tank and letting it stand for 10 min, and then using an LB film lifter to press the dispersion at a speed of 4.5 mm / min to obtain a Langmuir film with a surface pressure of 35 mN / m;
[0121] The distance between the quartz plate and the LB tank is 0.7 cm;
[0122] (4) Using a clamp, the quartz plate in step (3) is lifted at a constant speed of 35 mN / m and 5.5 mm / min, so that the Langmuir film in step (3) is transferred to the quartz plate. After the quartz plate is completely lifted out of the water, the film lifting is stopped and the film is allowed to stand for 10 minutes to obtain the core nanofilm (such as Figure 8 shown);
[0123] There is no particular order in which steps (1) and (2) are performed.
[0124] Example 5
[0125] This embodiment provides a method for preparing a core nanofilm, the preparation method comprising:
[0126] (1) 5 g of core was ball-milled at a speed of 400 r / min for 260 min, with a 10-min break after every 60 min of grinding to obtain core particles with a size of 950 nm, which were then added to chloroform and mixed under ultrasound for 30 min to obtain a dispersion with a concentration of 0.02 mg / mL;
[0127] (2) After cutting a quartz sheet of 25×40 mm into pieces of 12.5×40 mm, the quartz sheet was subjected to a first cleaning treatment, plasma bombardment of the surface of the quartz sheet for 10 min, and a second cleaning treatment to obtain a hydrophilically modified quartz sheet;
[0128] The steps of the first cleaning process and the second cleaning process are the same as those in Example 1;
[0129] (3) vertically immersing the quartz plate obtained in step (2) into water at a depth of 1.5 cm, using a microsyringe to absorb 100 μL of the dispersion obtained in step (1), spreading it on the water surface of the LB tank and letting it stand for 10 min, and then using an LB film lifter to press the dispersion at a speed of 1.5 mm / min to obtain a Langmuir film with a surface pressure of 25 mN / m;
[0130] The distance between the quartz plate and the LB tank is 0.7 cm;
[0131] (4) Using a clamp, the quartz plate in step (3) is lifted at a constant speed of 10.5 mm / min at a pressure of 25 mN / m, so that the Langmuir film in step (3) is transferred to the quartz plate. After the quartz plate is completely lifted out of the water, the film lifting is stopped and the film is allowed to stand for 10 minutes to obtain the core nanofilm (such as Fig. 9 shown);
[0132] There is no particular order in which steps (1) and (2) are performed.
[0133] Example 6
[0134] This embodiment provides a method for preparing a core nanofilm, the preparation method comprising:
[0135] (1) 2 g of core was ball-milled at a speed of 500 r / min for 240 min, with a 5-min break after every 60 min of grinding to obtain core particles with a size of 400 nm, which were then added to chloroform and mixed under ultrasound for 30 min to obtain a dispersion with a concentration of 0.08 mg / mL;
[0136] (2) After cutting a 25×40 mm mica sheet into 12.5×40 mm pieces, the mica sheet is subjected to a first cleaning treatment, plasma bombardment of the surface of the mica sheet for 10 min, and a second cleaning treatment in sequence to obtain a hydrophilically modified mica sheet;
[0137] The steps of the first cleaning process and the second cleaning process are the same as those in Example 1;
[0138] (3) vertically immersing the mica sheet obtained in step (2) into the water at a depth of 2 cm, using a microsyringe to absorb 50 μL of the dispersion obtained in step (1), and spreading it on the water surface of the LB tank and letting it stand for 10 min, then using an LB film lifter to press the dispersion at a speed of 40 mm / min to obtain a Langmuir film with a surface pressure of 25 mN / m;
[0139] The distance between the mica sheet and the LB tank is 0.8 cm;
[0140] (4) Using a clamp, lift the mica sheet in step (3) at a pressure of 25 mN / m and a speed of 10 mm / min, so that the Langmuir film in step (3) is transferred to the mica sheet. After the mica sheet is completely lifted out of the water, the film lifting is stopped and the film is allowed to stand for 10 minutes to obtain the core nanofilm (such as Fig.10 shown);
[0141] There is no particular order in which steps (1) and (2) are performed.
[0142] Example 7
[0143] This embodiment provides a method for preparing a core nanofilm, the preparation method comprising:
[0144] (1) 2 g of core was ball-milled at a speed of 500 r / min for 240 min, with a 1 min break after every 60 min of grinding to obtain core particles with a size of 360 nm, which were then added to chloroform and mixed under ultrasound for 30 min to obtain a dispersion with a concentration of 0.01 mg / mL;
[0145] (2) After cutting a 25×40 mm silicon single wafer into 12.5×40 mm pieces, the single wafer is subjected to a first cleaning treatment, plasma bombardment of the silicon single wafer surface for 10 min, and a second cleaning treatment in sequence to obtain a hydrophilically modified silicon single wafer;
[0146] The steps of the first cleaning process and the second cleaning process are the same as those in Example 1;
[0147] (3) vertically immersing the silicon single crystal obtained in step (2) into water at a depth of 2 cm, using a microsyringe to absorb 250 μL of the dispersion obtained in step (1), spreading it on the water surface of the LB tank and letting it stand for 10 min, and then using an LB film lifter to press the dispersion at a speed of 5 mm / min to obtain a Langmuir film with a surface pressure of 30 mN / m;
[0148] The distance between the silicon single crystal and the LB tank is 0.7 cm;
[0149] (4) Using a clamp, lift the silicon single crystal wafer of step (3) at a pressure of 30 mN / m and a speed of 5 mm / min, so that the Langmuir film of step (3) is transferred to the silicon single crystal wafer. After the silicon single crystal wafer is completely lifted out of the water, the film lifting is stopped and the film is left to stand for 10 minutes to obtain the core nanofilm (such as Fig.11 shown);
[0150] There is no particular order in which steps (1) and (2) are performed.
[0151] Example 8
[0152] This embodiment provides a method for preparing a core nanofilm, the preparation method comprising:
[0153] (1) 3 g of core was ball-milled at a speed of 500 r / min for 300 min, with a 5-min break after every 60 min of grinding to obtain core particles with a size of 350 nm, which were then added to chloroform and mixed under ultrasound for 30 min to obtain a dispersion with a concentration of 0.02 mg / mL;
[0154] (2) After cutting a 25×40 mm Cu sheet into 12.5×40 mm pieces, the Cu sheet was subjected to a first cleaning treatment, plasma bombardment of the Cu sheet surface for 10 min, and a second cleaning treatment in sequence to obtain a hydrophilically modified Cu sheet;
[0155] The first cleaning process is: cleaning the Cu sheet with a large amount of distilled water, then putting it into a beaker and adding ethanol until the Cu sheet is immersed, then putting the beaker into an ultrasonic cleaner and shaking for 20 minutes, taking out the Cu sheet and cleaning the surface with distilled water;
[0156] The second cleaning treatment is: placing the Cu sheet in ethanol for ultrasonic treatment for 20 minutes, then cleaning its surface with distilled water, and then ultrasonically cleaning it in distilled water for 20 minutes;
[0157] (3) The Cu sheet obtained in step (2) was vertically immersed in water at a depth of 2 cm, 150 μL of the dispersion obtained in step (1) was drawn using a microsyringe, and spread on the water surface of the LB tank and allowed to stand for 10 min, and then the dispersion was pressed at a speed of 40 mm / min using an LB film lifter to obtain a Langmuir film with a surface pressure of 5 mN / m;
[0158] The distance between the Cu sheet and the LB tank is 0.75 cm;
[0159] (4) Using a clamp, lift the Cu sheet in step (3) at a pressure of 5 mN / m and a speed of 10 mm / min, so that the Langmuir film in step (3) is transferred to the Cu sheet. After the Cu sheet is completely lifted out of the water, the film lifting is stopped and allowed to stand for 10 minutes to obtain the core nanofilm (such as Fig.12 shown);
[0160] There is no particular order in which steps (1) and (2) are performed.
[0161] Examples 9-13
[0162] Examples 9-13 provide a method for preparing a core nanofilm. Except for some related parameters that are different from those in Example 8 (as shown in Table 1), other conditions in the preparation method are the same as those in Example 8.
[0163] Table 1
[0164]
[0165]
[0166] The optical photographs of the core nanofilm samples obtained in Examples 9-13 are as follows: Figure 13-17 shown.
[0167] Embodiment 14
[0168] This embodiment provides a method for preparing a core nanofilm. Except that the concentration of the dispersion in step (1) is 0.005 mg / mL, other conditions are the same as those in Example 1.
[0169] Embodiment 15
[0170] This embodiment provides a method for preparing a core nanofilm. Except that the concentration of the dispersion in step (1) is 0.10 mg / mL, other conditions are the same as those in Example 1.
[0171] Example 16
[0172] This embodiment provides a method for preparing a core nanofilm. Except that the distance between the quartz plate and the LB tank in step (3) is 2 cm, other conditions are the same as those in Example 1.
[0173] Embodiment 17
[0174] This embodiment provides a method for preparing a core nanofilm. Except that the surface pressure of the Langmuir film in step (3) and the lifting pressure in step (4) are both 2 mN / m, other conditions are the same as those in Example 1.
[0175] Embodiment 18
[0176] This embodiment provides a method for preparing a core nanofilm. Except that the surface pressure of the Langmuir film in step (3) and the lifting pressure in step (4) are both 40 mN / m, other conditions are the same as those in Example 1.
[0177] Comparative Example 1
[0178] This comparative example provides a method for preparing a core nanofilm. Except that the dispersion liquid is not subjected to film pressing in step (2), other conditions are the same as those in Example 1.
[0179] The wettability contact angle measurement experiment was conducted on the core nanofilms prepared in Examples 1-5, Examples 14-18 and Comparative Example 1, and the wettability of the core nanofilms was directly measured using a conventional contact angle method;
[0180] Test method for simulated contact angle:
[0181] By constructing a model, the spreading process of a drop of homogeneous liquid falling on a plane in the air is simulated; the entire simulation calculation area is 2cm×2cm, the droplet is directly above the geometric center and then drips, and the volume of each droplet is 4uL; at the same time, plane curve data is randomly generated, and then planes of different thicknesses are constructed respectively, and the data of planes of different thicknesses are imported into COMSOL geometric data; then a simulation experiment is carried out, and the contact angle values of surfaces of different thicknesses are obtained through simulation.
[0182] Among them, according to the physical model, the simulated contact angle has the following assumptions:
[0183] (1) There is no physical or chemical reaction between the solid surface and the liquid being tested, the solid surface is adiabatic, and the contact surface temperature remains constant;
[0184] (2) The experiment selected incompressible fluid, the physical model referred to pure water, and the flow conformed to the laminar flow law;
[0185] (3) Liquid does not absorb onto the surface of the solid and does not penetrate into the interior of the solid.
[0186] The calculated simulated contact angle values and the average contact angle values of the LB core particle nanofilm obtained experimentally are shown in Table 2.
[0187] Table 2
[0188]
[0189]
[0190] From Table 2, we can draw the following conclusions:
[0191] (1) The core nanofilm prepared by the preparation method provided in Examples 1-5 of the present invention is dense and uniform, and can directly describe the wettability of the reservoir. The error between the simulated contact angle value and the experimentally measured average contact angle value is within 5°, which can accurately reflect the wettability of the rock formation.
[0192] (2) It can be seen from the comparison between Example 1 and Examples 14-15 that when the concentration of the dispersion is too low, the core nanoparticles present in the dispersion are small in number, so that the core nanoparticles cannot form a continuous film after compression; when the concentration of the dispersion is too high, the core nanoparticles cannot be evenly spread, resulting in large fluctuations in the measured contact angle values;
[0193] (3) From the comparison between Example 1 and Example 16, it can be seen that when the distance between the solid substrate and the LB tank is too large, the solid substrate is pulled for too long, and the deposited film is exposed to the air for too long, making the core nanofilm too dry, and a certain number of bubbles are captured and invaded by the film pores;
[0194] (4) From the comparison between Example 1 and Examples 17-18, it can be seen that when the surface pressure of the Langmuir film and the pressure during film lifting are too small, the horizontal lateral pressure exerted by the sliding barrier of the water tank on the particles is small, so that the spacing between the particles of the core nanofilm is slightly large, and it is impossible to form a dense continuous film; when the surface pressure of the Langmuir film and the pressure during film lifting are too large, the horizontal lateral pressure exerted by the sliding barrier of the water tank on the particles is too large, so that the particles of the core nanofilm are closely stacked, and even double-layer or even multi-layer films are formed, but this does not affect the measurement of the contact angle and the subsequent qualitative judgment of wettability, but it is impossible to obtain a single-layer core nanofilm;
[0195] (5) By comparing Example 1 with Comparative Example 1, it can be seen that if the dispersion is not subjected to film pressing treatment, the particles are freely dispersed on the water surface due to the surface tension, so that the core nanoparticles cannot gather together and a film cannot be formed.
[0196] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a core nanofilm, characterized in that: The preparation method comprises: (1) mixing the ball-milled core with an organic solvent to obtain a dispersion; (2) vertically immersing the hydrophilically modified solid substrate under the liquid surface, spreading the dispersion obtained in step (1) on the liquid surface of the LB tank and allowing it to stand, and then performing a film pressing process on the dispersion to obtain a Langmuir film; (3) Lifting the solid substrate described in step (2) so that the Langmuir film described in step (2) is transferred to the solid substrate, and the core nanofilm is obtained after standing.
2. The preparation method according to claim 1, characterized in that: When performing the ball milling in step (1), the injection amount of the core is 2-5 g; Preferably, the rotation speed of the ball mill in step (1) is 350-500 r / min; Preferably, the ball milling time in step (1) is 195-325 min.
3. The preparation method according to claim 1 or 2, characterized in that: After ball milling in step (1), the size of the core is 350-950 nm; Preferably, the organic solvent in step (1) comprises chloroform; Preferably, the mixing in step (1) is performed under ultrasound; Preferably, the mixing time in step (1) is 25-35 min; Preferably, the concentration of the dispersion in step (1) is 0.01-0.08 mg / mL.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The material of the solid substrate in step (2) includes any one of a quartz sheet, a conductive glass, a silicon single crystal sheet, a mica sheet or a metal sheet; Preferably, the conductive glass comprises ITO conductive glass and / or FTO conductive glass; Preferably, the metal sheet includes any one of a Cu sheet, a Ti sheet, a Ni sheet or an Al sheet; Preferably, the method for hydrophilic modification of the solid substrate in step (2) comprises: sequentially performing a first cleaning treatment, a plasma treatment and a second cleaning treatment on the solid substrate; Preferably, the plasma treatment is: bombarding the surface of the solid substrate with plasma for 8-12 minutes.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), the solid matrix is vertically immersed in the liquid to a depth of 1-5 cm; Preferably, the distance between the solid matrix and the LB tank in step (2) is 0.5-1 cm; Preferably, the volume of the dispersion in step (2) is 50-250 μL; Preferably, the standing time in step (2) is ≥ 10 min.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The speed of the lamination process in step (2) is 5-80 mm / min; Preferably, the surface pressure of the Langmuir film in step (2) is 5-35 mN / m.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The lifting pressure in step (3) is 5-35 mN / m; Preferably, the lifting speed in step (3) is 1.5-22.5 mm / min; Preferably, the end point of lifting in step (3) is: all the solid matrix is lifted to the water surface; Preferably, the standing time in step (3) is ≥ 10 min; Preferably, the thickness of the core nanofilm in step (3) is less than 1000 nm.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises: (1) ball milling the core at a speed of 350-500 r / min for 195-325 min to obtain core particles with a size of 350-950 nm, and then mixing the organic solvent and the core particles under ultrasound for 25-35 min to obtain a dispersion with a concentration of 0.01-0.08 mg / mL; (2) vertically immersing the hydrophilically modified solid substrate under the liquid surface, spreading 50-250 μL of the dispersion obtained in step (1) on the liquid surface of the LB tank and letting it stand for ≥10 min, and then pressing the dispersion at a speed of 5-80 mm / min to obtain a Langmuir film with a surface pressure of 5-35 mN / m; The depth of the solid matrix vertically immersed in the liquid surface is 1.5-5 cm; the distance between the solid matrix and the LB tank is 0.5-1 cm; (3) The solid substrate of step (2) is lifted at a pressure of 5-35 mN / m and a speed of 1.5-22.5 mm / min, so that the Langmuir film of step (2) is transferred to the solid substrate, until the solid substrate is completely lifted out of the water surface, and then the solid substrate is allowed to stand for ≥10 min to obtain a core nanofilm with a thickness of less than 1000 nm.
9. A core nanofilm, characterized in that: The core nanofilm is prepared by the preparation method according to any one of claims 1 to 8; The thickness of the core nano film is less than 1000 nm.
10. An application of the core nanofilm as claimed in claim 9, characterized in that: The core nanofilm is used for evaluating rock wettability.